An Insight Into the Intestinal Web of Mucosal Immunity, Microbiota, and Diet in Inflammation - Yap, Yu Anne; Mariño, Eliana (Frontiers in Immunology, 2018)
The rising global incidence of autoimmune and inflammatory conditions can be attributed to changes in the large portion of the immune system that belongs to our gastrointestinal tract (GI). The intestinal immune system serves as a gatekeeper to prevent pathogenic invasions and to preserve a healthier gut microbiota. The gut microbiota has been increasingly studied as a fundamental contributor to the state of health and disease. From food fermentation, the gut microbiota releases metabolites or short chain fatty acids (SCFAs), which have anti-inflammatory properties and preserve gut homeostasis. Immune responses against food and microbial antigens can cause inflammatory disorders such as inflammatory bowel disease (IBD) and celiac disease. As such, many autoimmune and inflammatory diseases also have a “gut origin”. A large body of evidence in recent years by ourselves and others has uncovered the link between the immune system and the SCFAs in specific diseases such as autoimmune type 1 diabetes (T1D), obesity and type 2 diabetes (T2D), cardiovascular disease, infections, allergies, asthma, and IBD. Thus, the power of these three gut dynamic components—the mucosal immunity, the microbiota, and diet—can be harnessed in tandem for the prevention and treatment of many inflammatory and infectious diseases.